ch3 boolean algebra (cont...

27
ACCESS IC LAB Graduate Institute of Electronics Engineering, NTU CH3 Boolean Algebra (cont CH3 Boolean Algebra (cont d) d) Lecturer:吳安宇 Date2005/10/7

Upload: others

Post on 18-Mar-2020

2 views

Category:

Documents


0 download

TRANSCRIPT

ACCESS IC LAB

Graduate Institute of Electronics Engineering, NTU

CH3 Boolean Algebra (contCH3 Boolean Algebra (cont’’d)d)

Lecturer:吳安宇

Date:2005/10/7

Graduate Institute of Electronics Engineering, NTU

pp. 2

IntroductionIntroductionv Today, you’ll know:

1. Guidelines for multiplying out/factoring expressions2. Exclusive-OR and Equivalence operations3. Positive logic and negative logic4. More about consensus theorem5. Algebraic simplification of switching expressions6. Approach to prove validity of an equation7. The difference between ordinary algebra and

Boolean algebra

Graduate Institute of Electronics Engineering, NTU

pp. 3

Guidelines for Multiplying Out and Guidelines for Multiplying Out and FactoringFactoring

vUse X(Y+Z) = XY + XZ ...(1)(X+Y)(X+Z) = X + YZ ...(2)(X+Y)(X’+Z) = XZ + X’Y ...(3)

vFor multiplying out, (2) and (3) should be generally applied before (1) to avoid generating unnecessary termsvFor factoring, apply (1), (2), (3) from right terms to

left terms

Graduate Institute of Electronics Engineering, NTU

pp. 4

Multiplying Out ExpressionMultiplying Out Expression

EX. F = (Q + AB)(C’D + Q’) = QC’D + Q’ABor F = QC’D + QQ’ + AB’C’D + AB’Q’

EX. (A+B+C’)(A+B+D)(A+B+E)(A+D’+E)(A’+C)= (A+B+C’D)(A+B+E)[AC+A’(D’+E)]

= (A+B+C’DE)(AC+A’D’+A’E)= AC+ABC+A’BD’+A’BE+A’C’DE (SOP form)

=> By brute force => 162 terms

Distributed Law

Graduate Institute of Electronics Engineering, NTU

pp. 5

Factoring ExpressionFactoring Expression

v EX.AC + A’BD’ + A’BE + A’C’DE

= AC + A’(BD’ + BE + C’DE)XZ + X’Y = (X + Y)(X’ + Z)

= (A + BD’ + BE + C’DE)(A’ + C)= [ A + C’DE + B (D’ + E) ](A’ + C)

X + YZ = (X+Y)(X+Z)= (A + C’DE + B)(A + C’DE + D’ + E)(A’ + C)= (A + B + C’)(A + B + D)(A + B + E)(A + D’ + E)(A’ + C)

Graduate Institute of Electronics Engineering, NTU

pp. 6

3.2 Exclusive3.2 Exclusive--OR OperationsOR OperationsvExclusive-OR (XOR)

X Y X Y0 00 11 01 1

0110

Truth TableSymbol

Boolean Expression : X Y = X’Y + XY’

Graduate Institute of Electronics Engineering, NTU

pp. 7

ExclusiveExclusive--OR OperationsOR Operations

vUseful Theorems :

X 0 = X X Y = Y X (commutative)

X 1 = X’ (X Y) Z = X (Y Z) (associative)

X X = 0 X(Y Z) = XY XZ (distributive)

X X’= 1 (X Y)’ = X Y’ = X’ Y = XY + X’Y’

Graduate Institute of Electronics Engineering, NTU

pp. 8

Proof of Distributive LawsProof of Distributive LawsvXY XZ = XY(XZ)’ + (XY)’XZ

= XY(X’ + Z’) + (X’ + Y’)XZ= XYZ’ +XY’Z= X(YZ’ + Y’Z)= X(Y Z)

Graduate Institute of Electronics Engineering, NTU

pp. 9

Equivalence Operations Equivalence Operations (Exclusive NOR)(Exclusive NOR)

X Y X Y (X Y)’0 00 11 01 1

1001

1001

X Y = XY + X’Y’

Graduate Institute of Electronics Engineering, NTU

pp. 10

Simplification of XOR and XNORSimplification of XOR and XNORvX Y = X’Y + XY’

X Y = X’Y’ + XY

n EX (see p.62). F = (A’B C) + (B AC’)

= [(A’B)C + (A’B)’C’] + [B’(AC’) + B(AC’)’]= A’BC + (A+B’)C’ + AB’C’ + B(A’ +C)= B(A’C + A’ + C) + C(A + B’ + AB’)= B(A’ + C) + C’(A + B’) ( can be further simplified)

Graduate Institute of Electronics Engineering, NTU

pp. 11

3.3 Consensus Theorem3.3 Consensus TheoremXY + X’Z + YZ = XY + X’Z (YZ is redundant )

Proof : XY + X’Z + YZ = XY + X’Z + (X + X’)YZ

= (XY + XYZ) + (X’Z + X’YZ)= XY(1 + Z) + X’Z(1 + Y)= XY + X’Z

Graduate Institute of Electronics Engineering, NTU

pp. 12

How to Find Consensus Term?How to Find Consensus Term?1. Find a pair of terms, one of which contains a

variable and the other contains its complement

A’C’D + A’BD + BCD + ABC + ACD’ (A ↔ A’)

2. Ignore the variable and its complement, the left variables composite the consensus term

(A’BD) + (ABC) → BD·BC = BCD (redundant term)

Graduate Institute of Electronics Engineering, NTU

pp. 13

Consensus TheoremConsensus TheoremvApplication to eliminate redundant terms from

Boolean Expressions

a’b’ + ac + bc’ + b’c +ab = a’b’ + ac + bc’

Graduate Institute of Electronics Engineering, NTU

pp. 14

Consensus TheoremConsensus Theorem

Example (others are on p.67) :

(a + b + c’)(a + b + d’)(b + c + d’)= (a + b + c’)(b + c + d’)

n Simplification of Boolean Expression can reduce the cost of realizing the network using gates

nDual form of consensus theorem(X + Y)(X’ + Z)(Y + Z) = (X + Y)(X’ + Z)

(a+ b + c’) + (b + c +d’) → a+b + b+d’ = a+b+d’

Graduate Institute of Electronics Engineering, NTU

pp. 15

Algebraic Simplification of Switching Algebraic Simplification of Switching ExpressionExpression

vA. Combining TermsXY + XY’ =X(Y + Y’) = X

n EX.1 abc’d’ + abcd’ = abd’ (X = abd’, Y = c)n EX.2 ab’c + abc + a’bc

= ab’c + abc + abc + a’bc = ac + bc

n EX.3 (a + bc)(d + e’) + a’(b’ + c’)(d + e’)= d + e’

Graduate Institute of Electronics Engineering, NTU

pp. 16

Algebraic Simplification of Switching Algebraic Simplification of Switching ExpressionExpression

vRule B -- Eliminating Terms : X + XY = XXY + X’Z + YZ = XY + X’Z

n EX.1 a’b + a’bc = a’b (X = a’b)

a’bc’ + bcd + a’bd = a’bc’ + bcd (X = c, Y = bd, Z = a’b)

Graduate Institute of Electronics Engineering, NTU

pp. 17

Algebraic Simplification of Switching Algebraic Simplification of Switching ExpressionExpression

vRule C -- Eliminating Literals : X + X’Y = (X + X’)(X + Y) = X + Y

n EX. A’B + A’B’C’D’ + ABCD’= A’(B + B’C’D’) + ABCD (common term - A’)= A’(B + C’D’) + ABCD (Rule C)= B(A’ + ACD) + A’C’D’ (common term - B)= B(A’ + CD) + A’C’D’ (Rule C)= A’B + BCD’ + A’C’D’ (final terms)

Graduate Institute of Electronics Engineering, NTU

pp. 18

Algebraic Simplification of Switching Algebraic Simplification of Switching ExpressionExpression

vRule D -- Adding Redundant Terms

vAdd XX’ = 0

vMultiply by (X + X’) = 1

vAdd YZ to (XY + X’Z) (reverse of Consensus)

ØBecause XY + X’Z + YZ = XY + X’Z

vAdd XY to X

Graduate Institute of Electronics Engineering, NTU

pp. 19

Algebraic Simplification of Switching Algebraic Simplification of Switching ExpressionExpression

vEX.1 of “Adding Redundant Terms”

WX + XY + X’Z’ + WY’Z = WX + XY + X’Z’ + WY’Z’ + W’Z

(add W’Z by Consensus Theorem)= WX + XY + X’Z’ + WZ’

(eliminate WY’Z’ by WZ’)= WX + XY + X’Z’

Graduate Institute of Electronics Engineering, NTU

pp. 20

Algebraic Simplification of Switching Algebraic Simplification of Switching ExpressionExpression

n EX.2 A’B’C’D’ + A’BC’D’ + A’BD + A’BC’D + ABCD + ACD’+ B’CD’

= A’C’D’ + A’BD + B’CD’ + ABC(A, B, C, D methods are applied)n No easy way to determine when a Boolean

Expression has a min. no. of terms or literalsn Systematic way is presented in Ch.5 & CH.6

Graduate Institute of Electronics Engineering, NTU

pp. 21

Proving Validity of an EquationProving Validity of an Equation

vApproach : vConstruct a Truth TablevManipulate one side of the equation till it’s

identical to the other sidevReduce both sides independently to the same

equationv(a) Perform same operation on both sides

(b) Cannot Subtract or Divide both sides(Subtraction, Division NOT defined)

Graduate Institute of Electronics Engineering, NTU

pp. 22

Proving Validity of an EquationProving Validity of an Equation

vUsually :vReduce both sides to Sum of Products (SOP)vCompare both sidesvTry to Add or Delete terms by using Theorems

Graduate Institute of Electronics Engineering, NTU

pp. 23

Proving Validity of an EquationProving Validity of an EquationvEX.1 Show that

A’BD’ + BCD + ABC’ + AB’D = BC’D’ + AD + A’BC

By Consensus Theorem : A’BD’ + BCD + ABC’ + AB’D + BC’D’ + A’BC + ABD

= AD + A’BD’ + BCD + ABC’ + BC’D’ + A’BC

= AD + BC’D’ + A’BC

1 2 31 + 2 1 + 3 2 + 3

Graduate Institute of Electronics Engineering, NTU

pp. 24

Proving Validity of an EquationProving Validity of an Equation

vEX.2 Show A’BC’D + (A’ + BC)(A + C’D’) + BC’D + A’BC’

= ABCD + A’C’D’ + ABD + ABCD’ + BC’D

nReducing the left side

A’BC’D + (A’ + BC)(A + C’D’) + BC’D + A’BC’

= (A’ + BC)(A + C’D’) + BC’D + A’BC’

= ABC + A’C’D’ + BC’D + A’BC’

= ABC + A’C’D’ + BC’D

Graduate Institute of Electronics Engineering, NTU

pp. 25

Proving Validity of an EquationProving Validity of an Equation

vEX.2(cont.)vReducing the left side

ABCD + A’C’D’ + ABD + ABCD’ + BC’D

= ABC + A’C’D’ + ABD + BC’D

= ABC + A’C’D’ + BC’DnBecause both sides were independently reduced

to the same expression, the original equation is valid

Graduate Institute of Electronics Engineering, NTU

pp. 26

Boolean Algebra & Ordinary AlgebraBoolean Algebra & Ordinary AlgebravBoolean Algebra ≠ Ordinary AlgebraEX.1 X + Y = X + Z => Y = Z (?)

X = 1, Y = 0 => 1 + 0 = 1 + 1But 0 ≠ 1

EX.2 “If XY = XZ then Y = Z”True : when X ≠ 0False : when X = 0

Graduate Institute of Electronics Engineering, NTU

pp. 27

Boolean Algebra & Ordinary AlgebraBoolean Algebra & Ordinary Algebra

vEX.3 if Y = Z then X + Y = X + Z (V)if Y = Z then XY = XZ (V)

n Add/Multiply the same term => Validn Subtract/Divide the same term => Not Valid

n Check programmed exercise 3.1, 3.2,…,3.5 for practice